HUBUNGAN PENGETAHUAN TENTANG APD PEMBUATAN TAHU TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI OLEH PEKERJA PABRIK TAHU WARDI DI JL.CIPTA KARYA DAN PAYUNG SEKAKI KOTA PEKANBARU 2020 - Neneng Neng Sanjaya; Putri Wulandini; Roni Saputra (Jurnal Keperawatan Abdurrab, 2020)
This study aims to determine whether there is a Knowledge Relationship about Tofu Makers to the Use of Personal Protective Equipment by Tofu Factory Workers at Jl.Cipta Karya and Kec.Payung Sekaki Pekanbaru City. The method of collecting data in this study through observation and questionnaire methods and library research to in this study were 38 Tofu factory workers on Jl.Cipta Karya and Kec.Payung Sekaki Pekanbaru City. The Sampling Technique used was the Total Sampling Technique, Total Sampling was a sampling technique where the number of samples was equal to the total population (Sugiono, 2011). The results of the analysis do not have a relationship between knowledge and the use of PPE proven in the data analysis shows that there were 30 people or 78.9% who did not use PPE completely and it could be stated that their knowledge was lacking.